1995
DOI: 10.1063/1.359411
|View full text |Cite
|
Sign up to set email alerts
|

Properties of amorphous diamond films prepared by a filtered cathodic arc

Abstract: Amorphous diamond films have been prepared by filtered cathodic arc deposition of carbon. The filtered arc is well suited for the growth of amorphous diamond, as it provides carbon ions with optimum kinetic energies at practical deposition rates. These films contain no hydrogen and are therefore structurally different from diamond-like carbon films generated by plasma chemical vapor deposition. Diamond-type bonding of carbon is quantitatively determined by electron energy loss spectroscopy, as an sp3 content u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(47 citation statements)
references
References 41 publications
4
40
0
Order By: Relevance
“…On the other hand, density determinations via EELS rely on an effective electron mass, for which different values can be found in literature [7][8][9]. We will show how a correct fit of the plasmon peak and an appropriate choice of the effective mass can give good agreement with the XRR mean densities, thus validating the use of the quasi-free electron model to analyse the low loss spectrum.…”
Section: Introductionmentioning
confidence: 87%
“…On the other hand, density determinations via EELS rely on an effective electron mass, for which different values can be found in literature [7][8][9]. We will show how a correct fit of the plasmon peak and an appropriate choice of the effective mass can give good agreement with the XRR mean densities, thus validating the use of the quasi-free electron model to analyse the low loss spectrum.…”
Section: Introductionmentioning
confidence: 87%
“…The virtual spectrum of each pyrocarbon can be compared to the isotropic-like virtual spectrum obtained from a graphite single crystal (100% sp 2 ) using the same process (i.e., with single crystals having random orientation). The sp 2 content of the pyrocarbon is subsequently calculated from more conventional calculation [15] and [16].…”
Section: Electron Energy Loss Spectroscopymentioning
confidence: 99%
“…Amorphous carbon films (a-C) that have more than 80% tetrahedral (sp 3 ) bonding are referred to as tetrahedral amorphous carbon (ta-C) [7,9,19], or sometimes even as "amorphous diamond." [20,21] There are large variations even within each class of materials, depending on the method and parameters of deposition. Diamond-like carbon films can be synthesized by argon sputter deposition using a graphite target [12,22] [6,16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] There are large variations even within each class of materials, depending on the method and parameters of deposition. Diamond-like carbon films can be synthesized by argon sputter deposition using a graphite target [12,22] [6,16,20,21]. Research over the last years has identified filtered cathodic arc deposition as one of the promising techniques for hard carbon films thinner than 5 nm [28,29].…”
Section: Introductionmentioning
confidence: 99%